2018
DOI: 10.1002/jcb.27701
|View full text |Cite
|
Sign up to set email alerts
|

Protein translation associated to PERK arm is a new target for regulation of metainflammation: A connection with hepatocyte cholesterol

Abstract: Endoplasmic reticulum stress is a cellular phenomenon that has been associated with metabolic disorders, contributing to the development of obesity, fatty liver disease, and dyslipidemias. Under metabolic overload conditions, in cells with a high protein-secretory activity, such as hepatocytes and Langerhans β cells, the unfolded protein response (UPR) is critical in to maintain protein homeostasis (proteostasis). UPR integrated by a tripartite signaling system, through activating transcription factor 6, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…It is likely that a competition between oleic and palmitic acid for receptors such as FFAR1 or CD36 might occur; in fact, CD36 facilitates fatty acid transport and overexpression affects insulin secretion [48]. In an important way, we previously reported that small molecules with terpene structure could regulate ER stress induced by PA, through inhibition of the eukaryotic initiation factor-4A, with an effect in CHOP and XBP1s expression [49]. Therefore, protein translation is a target that could modulate ER stress induced by lipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that a competition between oleic and palmitic acid for receptors such as FFAR1 or CD36 might occur; in fact, CD36 facilitates fatty acid transport and overexpression affects insulin secretion [48]. In an important way, we previously reported that small molecules with terpene structure could regulate ER stress induced by PA, through inhibition of the eukaryotic initiation factor-4A, with an effect in CHOP and XBP1s expression [49]. Therefore, protein translation is a target that could modulate ER stress induced by lipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although free fatty acid proportions in the diet are a condition associated with the development of several diseases associated with alterations in metabolism [16,38,49], it is important to consider the adipose tissue as a buffering of lipid fluxes, which could be impaired in obesity by defects in response to the dynamic metabolism that occurs after meals [52], then modifying the relationship in concentrations of saturated/unsaturated plasmatic fatty acids. Therefore, the characterization of the main effects fatty acids have upon pancreatic β-cell physiology and the UPR pathway, and the repercussion on calcium homeostasis and insulin release, allow us to broaden our understanding of the different roles of fatty acids inside β-cells, which are important metabolites to take into account in explaining the damage and treatment of novel therapeutic targets in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by previous reports from our group where docking techniques were applied with good results [47,48], in the present work, docking was employed to search possible imidazole receptors.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The three branches of UPR are essential in cell homeostasis to reduce ER stress and to ensure adequate synthesis of peptides such as insulin [20]. Indeed, in several reports, we have described the effect of metabolic overload on the dysregulation of UPR arms [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Given this situation, the initial events of misfolding and amyloid aggregation promote a cascade of pathological processes considered the hallmark in the progression of several chronic degenerative diseases [8][9][10][11][12][13] that might be associated with conditions related to metabolic overload [21,22]. Having this in mind, we herein characterized the role of lipid systems on the conformational transitions of the most aggregative C-terminal domain of hIAPP, and through a biomimetic approach, evaluated this condition on variants F 23 R and I 26 A that potentially could reduce aggregation.…”
Section: Introductionmentioning
confidence: 99%